2022
DOI: 10.3389/fpsyt.2022.1017888
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram based on lymphocyte subsets to distinguish bipolar depression from major depressive disorder

Abstract: ObjectiveBipolar depression (BD) and major depressive disorder (MDD) are both common affective disorders. The common depression episodes make it difficult to distinguish between them, even for experienced clinicians. Failure to properly diagnose them in a timely manner leads to inappropriate treatment strategies. Therefore, it is important to distinguish between BD and MDD. The aim of this study was to develop and validate a nomogram model that distinguishes BD from MDD based on the characteristics of lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…However, the majority of research attention remains focused on the predictive role of physiological indicators on depressive symptoms, and these factors were also screened for influences that could be included in the Nomogram by a combination of multivariate logistic regression and univariate logistic regression. [48][49][50] We wanted to build on this base as, on the one hand, we wanted to screen variables by combining machine learning methods (e.g., LASSO regression) and multivariate logistic regression to better identify independent predictors. On the other hand, we combined demographic variables from previous studies that were much this included in the Nomogram and on this basis selected some psychological variables and behavioral factors that may have an impact on depressive symptoms to be included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of research attention remains focused on the predictive role of physiological indicators on depressive symptoms, and these factors were also screened for influences that could be included in the Nomogram by a combination of multivariate logistic regression and univariate logistic regression. [48][49][50] We wanted to build on this base as, on the one hand, we wanted to screen variables by combining machine learning methods (e.g., LASSO regression) and multivariate logistic regression to better identify independent predictors. On the other hand, we combined demographic variables from previous studies that were much this included in the Nomogram and on this basis selected some psychological variables and behavioral factors that may have an impact on depressive symptoms to be included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The study leverages lymphocyte subpopulation-based features to predict the maladies with an accuracy exceeding 90% [11]. The samples for the clinical trials are obtained from peripheral blood, which is less invasive, reinforcing the validity of the proposed method.…”
Section: A Machine Learningmentioning
confidence: 94%
“…ML also provides a feasible platform to differentiate psychiatric disorders, a crucial role considering there are over 200 types of known mental health disorders. Su et al [11] illustrate the use of ML to distinguish major depressive disorder from bipolar depression.…”
Section: A Machine Learningmentioning
confidence: 99%
“… Maes M et al, 2021 [ 15 ] 25 21 CD3, CD4, CD8, CD71, CD69, CD25, CD152, CD154, FOXP3 Activated T effector, Tregs BD and anti-HCMV IgG levels significantly interact to decrease the expression of CD4 + CD25 + FOXP3 + T phenotypes. Su L et al, 2022 [ 136 ] 83 101 CD3, CD4, CD8, CD45 Th, Tc BD patients had greater CD3 + T cell levels than HC. The inclusion and exclusion criteria for the studies are shown in Supplementary Fig.…”
Section: T Lymphocytes and Bdmentioning
confidence: 99%